2016
DOI: 10.1007/s12039-016-1167-0
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of self-assembled water-nitrate cluster in a Co(III)-2,2′-bipyridine host: Synthesis, X-ray structure, DNA cleavage, molecular docking and anticancer activity

Abstract: A mononuclear cobalt(III) complex [Co(bpy) 2 Cl 2 ]NO 3 •2H 2 O (1) (bpy = 2,2-bipyridine) has been synthesized and crystallographically characterized. Self-assembly of the lattice water molecules from rectangular tetrameric water cluster interacts with nitrate anion along the c-axis forming a six membered hexagonal water-nitrate cluster. It presents a new mode of association of water molecules with nitrate molecules which is not predicted theoretically or found experimentally. The molecule effectively cleaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…The crystal data and selected bond lengths and angles are summarized in Tables 1 and 2 distances and the angles around the Co(III) ion were quite similar to those of cis-[CoCl2(bpy)2](X)•2H2O (X = Clor NO3 -). 6,7 Moreover, the lattice parameters were also similar to those of two other previous reported complexes 6,7 (Table S1). The Cl•••H-C contacts between a Cl(2) atom and two H atoms of the 3-and 3′-positions in the bpy(N(1),N(2)) ligand in an adjacent cation complex, and the π-π stacking contacts between a bpy(N(1),N(2)) ligand and another bpy(N(1),N(2)) ligand in an adjacent cation complex, were observed in the crystal to form 1-D cationic chains (Fig.…”
supporting
confidence: 84%
See 4 more Smart Citations
“…The crystal data and selected bond lengths and angles are summarized in Tables 1 and 2 distances and the angles around the Co(III) ion were quite similar to those of cis-[CoCl2(bpy)2](X)•2H2O (X = Clor NO3 -). 6,7 Moreover, the lattice parameters were also similar to those of two other previous reported complexes 6,7 (Table S1). The Cl•••H-C contacts between a Cl(2) atom and two H atoms of the 3-and 3′-positions in the bpy(N(1),N(2)) ligand in an adjacent cation complex, and the π-π stacking contacts between a bpy(N(1),N(2)) ligand and another bpy(N(1),N(2)) ligand in an adjacent cation complex, were observed in the crystal to form 1-D cationic chains (Fig.…”
supporting
confidence: 84%
“…It brought about an efficient cleavage of double-stranded DNA without the requirement of an external agent in a concentration-dependent manner. 6 Similar 1-D water-anion chains were also observed in the Cl-salt, 7 though it is not described in this report. These crystal structures of cis- 6,7 indicated that a complex cation, cis-[CoCl2(bpy)2] + , would have two kinds of 1-D chains in the crystal without depending on a kind of counter ion.…”
supporting
confidence: 66%
See 3 more Smart Citations